2018
DOI: 10.3390/ijms19103169
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regulatory Networks Are Activated during Cold Stress in Medicago sativa L.

Abstract: Cultivated alfalfa (Medicago sativa L.) is one of the most important perennial legume forages in the world, and it has considerable potential as a valuable forage crop for livestock. However, the molecular mechanisms underlying alfalfa responses to cold stress are largely unknown. In this study, the transcriptome changes in alfalfa under cold stress at 4 °C for 2, 6, 24, and 48 h (three replicates for each time point) were analyzed using the high-throughput sequencing platform, BGISEQ-500, resulting in the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…This study indicated that the key enzyme in the ROS-scavenging systems in the Longmu 806 variety was upregulated as a defense to resist low-temperature stress, and the upregulation of the SOD1 gene may be a special protective mechanism in the Longmu 806 variety. The SOD1 gene may reduce the root freezing damage directly by increasing the superoxide scavenging capacity or indirectly by increasing the flux of H 2 O 2 [7], thereby maintaining a high survival rate of the alfalfa in severe winter conditions. The SOD1 may be one of the reasons why the Longmu 806 variety has a higher winter survival rate than the Sardi variety.…”
Section: Tfs Involved In the Low-temperature Stress Responsementioning
confidence: 99%
See 2 more Smart Citations
“…This study indicated that the key enzyme in the ROS-scavenging systems in the Longmu 806 variety was upregulated as a defense to resist low-temperature stress, and the upregulation of the SOD1 gene may be a special protective mechanism in the Longmu 806 variety. The SOD1 gene may reduce the root freezing damage directly by increasing the superoxide scavenging capacity or indirectly by increasing the flux of H 2 O 2 [7], thereby maintaining a high survival rate of the alfalfa in severe winter conditions. The SOD1 may be one of the reasons why the Longmu 806 variety has a higher winter survival rate than the Sardi variety.…”
Section: Tfs Involved In the Low-temperature Stress Responsementioning
confidence: 99%
“…Plants can survive safely in winter and enhance freezing resistance through a low-temperature adaptation process [6]. Previous studies on the mechanisms of plant responses to low temperature have mainly focused on plant physiology, phytohormones, and changes in low temperature-induced gene expression by regulating transcription factors (TFs) [7]. Plants undergo various changes under low-temperature stress, and the key response to low-temperature stress depends on the activation of molecular networks involved in stress signal transduction pathways and the expression of specific sets of stress-related genes [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can survive safely in winter and enhance freezing resistance through low temperature adaptation process [9]. The study of plant low temperature adaptation mechanism mainly focuses on physiological, phytohormones, and transcription factor regulation of low temperature induced gene expression changes [10]. Plants adapt to various changes in low temperature stress, and the critical response to low temperature stress conditions depends on the activation of molecular networks involved in the expression and signaling of specific stress-related genes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies on differentially expressed genes of low temperature resistance of alfalfa varieties have also been reported. A recent study reported that transcriptome high-throughput sequencing technology has been used to analysis the expression of the gene of the seedling [10], taproots [41], and crown buds [42] of alfalfa, which provides valuable resources for functional genomics research on plant cold tolerance in the future. However, the understanding of genetic response information for low temperature stress was limited, since some of the previous studies only RNA-seq the seedling, taproots, and crown buds of alfalfa.…”
Section: Introductionmentioning
confidence: 99%